Improvement of microstructure and mechanical properties of Wire + Arc Additively Manufactured Ti-6Al-4V with Machine Hammer Peening. (2017) - Hönnige, Jan Roman; Colegrove, Paul; Williams, Stewart
Abstract: Inter-pass rolling is a cold-working technique to improve microstructure and associated mechanical properties in Ti-6Al-4V wire + arc additive manufacturing (WAAM) and other AM processes. Initially developed to eliminate residual stress and distortion in WAAM, rolling equipment is very cumbersome and the application is limited to simple features and geometries. To exploit the potential design freedom of AM processes, this study investigates the potential of novel machine hammer peening (MHP) tools to aid or replace rolling as inter-pass cold working technique, as these tools can be manipulated relatively easy with articulated robots. The MHP tool used in this study is the pneumatically powered FORGEfix XP by KWM tools GmbH. The cold working behaviour of the tool was assessed using a confocal microscope to measure the deformed surface geometry, EBSD plastic strain maps identify dislocations under the peened area, as well as hardness and residual stress profiles. After the tool characterisation, inter-pass peening was applied to Ti-6Al-4V WAAM walls. Residual stresses that typically occur in additive manufacturing seem to promote the potential of the tool, as the penetration depth was higher compared to the treatment of a stress-free specimen. The successfully achieved grain refinement has met the expectations and is reported in this study.